Threadfins of the world (family Polynemidae) : an annotated and i llustrated catalogue of polynemid species known to date - Motomura, Hiroyuki; Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2004)
Describes 41 species belonging to 8 genera. Introductory section inc ludes general remarks on habitat and fisheries of the family, a glossar y of technical terms, an illustrated key to each genus and all species, and a detailed account for all species. Species accounts include an il lustration of each species, scientific and vernacular names, and inform ation on habitat, biology, fisheries, size, relevant literature and dis tribution. Following the species accounts are a list of nominal species in the family, a table of species by major marine fishing areas, and c olor plates.
"FIR/Cat.3."
Includes bibliographical references (p. 100-108) and index.
Keywords: Polynemidae -- Classification; Polynemidae -- Identification